Тривалий час: оціночне поняття у ст. 146 Кримінального кодексу України - Саско О.; Sasko O. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
У статті розглядаються питання, пов’язані зі кваліфікуючою ознакою складу злочину, передбаченого ст. 146 КК України, а саме: викрадення людини, здійснюване протягом тривалого часу. «Тривалий час» є оціночним поняттям. А визначення оціночних ознак потрібно для того, щоб надати даній ознаці загальної конкретики, спрямування та зрозумілості меж використання. Автор вважає, що найбільш доречною є аргументована пропозиція щодо тлумачення поняття «протягом тривалого часу» у контексті кримінальної відповідальності за викрадення людини – це період часу понад три дні. Тому закріплення у чинному законодавстві аналізованої кваліфікуючої ознаки у такому викладі є необхідним. The article considers issues related to the qualifying feature of the crime under Art. 146 of the Criminal Code (CC) of Ukraine, acts carried out for a long time. In this norm, the legislator defined the concept of «long/lasting time» as a certain astronomical period during which the detention of the victim in captivity may increase the social danger. However, this rule does not define the time required to disclose the content of this valuation concept. Therefore, the definition of a qualifying feature automatically became the competence of law enforcement agencies and criminal law doctrine. The author argues that some formalization of the concept is necessary to give this feature a general specificity, direction, and clarity of its implication boundaries. The author suggests amending Article 146 of the Criminal Code of Ukraine with a note in which to determine that long time should be understood as the unlawful deprivation of liberty, lasting for more than three days
The Length of Time: an Evaluative Concept in Article 146 of the Criminal Code of Ukraine.
Keywords: незаконне позбавлення волі; викрадення людини; тривалий час; оціночне поняття; кваліфікуюча ознака; illegal/unlawful deprivation of liberty; kidnapping; long time; qualifying feature; evaluation concept